Effects of video-based learning and learning interest on physical fitness achievement outcomes - Aswil Yuli Zikri; Ardo Okilanda; Zulbahri Zulbahri; Sefri Hardiansyah (Journal of Educational and Learning Studies, 2026)
This study aimed to examine the effects of video-based learning media and students’ learning interest on physical fitness learning outcomes in physical education. A quasi-experimental study using a pretest–posttest control group design was conducted among Grade XI students at SMAN 3 Painan during the 2025/2026 academic year. Students were classified into high- and low-interest groups and assigned to either video-based or conventional instruction. Data were analyzed using descriptive statistics and independent-samples t-tests. The experimental group achieved a higher mean score (M = 15.75, SD = 3.37) than the control group (M = 14.07, SD = 3.15). Significant differences were also found among students with high and low learning interest levels. Video-based learning effectively improves physical fitness learning outcomes regardless of students’ learning interest levels.